(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2023)
Background: The aim of this study is to evaluate the management of intertrochanteric fracture of the femur using Proximal Femoral Nail Antirotation (PFNA). Materials and methods: Sixty patients of unstable pertrochanteric fractures were treated by closed reduction and internal fixation by proximal femoral nail antirotation from July 2015 to June 2017. Four patients were lost to follow-ups. The remaining 56 patients were followed for a mean period of 2 years. The results were evaluated by assessing the patients regarding their clinical and functional outcome at follow up as per kyle’s criteria Results: Peroperative failure to proximal head neck blade fixation (n-1) jamming of nail (n=2) and post operative lateral migration of head neck blade (n=1) and fracture related infection (n=1) were complications observed. End results were excellent in 46.34%, good in 36.58%, fair is 14.64% and poor in 2.43%. Conclusion: Proximal Femoral Nail Antirotation (PFNA) is the biomechanically and biologically suitable implant for the management of intertrochanteric fracture of the femur. JCMCTA 2020 ; 31 (1) : 64-70